Expression of human BRCA1 variants in mouse ES cells allows functional analysis of BRCA1 mutations - Chang, Suhwan (American Society for Clinical Investigation, 2009)

(untitled)
To date, inheritance of a mutant BRCA1 or BRCA2 gene is the best-established indicator of an increased risk of developing breast cancer. Sequence analysis of these genes is being used to identify BRCA1/2 mutation carriers, though these efforts are hampered by the high frequency of variants of unknown clinical significance (VUSs). Functional evaluation of such variants has been restricted due to lack of a physiologically relevant assay. In this study we developed a functional assay using mouse ES cells to study variants of BRCA1. We introduced BAC clones with human wild-type BRCA1 or variants into Brca1-null ES cells and confirmed that only wild-type and a known neutral variant rescued cell lethality. The same neutral variant was also able to rescue embryogenesis in Brca1-null mice. A test of several BRCT domain mutants revealed all to be deleterious, including a VUS. Furthermore, we used this assay to determine the effects of BRCA1 variants on cell cycle regulation, differentiation, and genomic stability. Importantly, we discovered that ES cells rescued by S1497A BRCA1 exhibited significant hypersensitivity after γ-irradiation. Our results demonstrate that this ES cell–based assay is a powerful and reliable method for analyzing the functional impact of BRCA1 variants, which we believe could be used to determine which patients may require preventative treatments.